Up-to-date methods for treatment of osteoporosis - Kołczewska, Aleksandra (Przewodnik Lekarza/Guide for GPs, 2007)
The article summarizes current knowledge about treatment of osteoporosis.There are three groups of agents in pharmacologic therapy: anti-resorptive, anabolic and mixed action agents. Vertebro- and kyphoplasty, rehabilitation are described too.